BOLLYWOOD ACTORS AND WEB SERIES A STUDY ON THE TREND OF BOLLYWOOD ACTORS APPEARING IN WEB SERIES - Mandeep Choursia (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Bollywood is the term given to Hindi Cinema. It is a formal name for the Indian film industry and every artist from this field like actors, singers, cinematographers, directors, producers, fashion designers are a part of it. Till now Bollywood has given many prominent faces to the audience but now the emergence of the digital platform, the popularity of web series is increasing with every passing year and thus the choice of popular actors too. They are trying their skills in online series as it is getting more recognition. The reason for the popularity is the youth who are spending more time on the internet. From last few years, many prominent actors became part of various web series on different online portals. In this study close observation is done on 2019 web series and popular Indian film actors who got portrayed in diverse characters. Also, critical analysis is done on the roles they are playing in web series.